Kamu Kurumlarında İş Analizi Çalışmaları: Muğla Üniversitesi Örneği(Studies of Job Analyzing in Public Institutions: A Case Study in Muğla University) - Edip ÖRÜCÜ; Mustafa MORTAŞ (Yönetim ve Ekonomi, 2005)
In the context of the effectiveness of organization activities, determining the limits and the characteristics of the works, departments and units, definition of the duties have crucial importance. Job analyses are done in order to carry out these aims. This study aims to determine the reactions of the employees to the job analyses done in the organizations. In this context, the study includes a literature survey on job analyses. The findings obtained from the field research have been analyzed. A questionnaire has been applied to employees in the Faculty of Economic and Administrative Sciences and the Faculty of Arts and Sciences in Muğla University. Consequently, we find that the reaction of the employees in the Faculty of Economic and Administrative Sciences is less than the others, depending on that they know much more about job analyses.